2008
DOI: 10.1099/vir.0.2008/004101-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence for homologous recombination within the family Birnaviridae

Abstract: Birnaviruses are bi-segmented double-stranded RNA (dsRNA) viruses infecting insects, avian species and a wide range of aquatic species. Although homologous recombination is a common phenomenon in positive-sense RNA viruses, recombination in dsRNA viruses is rarely reported. Here we performed a comprehensive survey on homologous recombination in all available sequences (.1800) of the family Birnaviridae based on phylogenetic incongruence. Although inter-species recombination was not evident, potential intra-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
(41 reference statements)
2
28
0
3
Order By: Relevance
“…In fact, Tong et al (1993) showed that IBD was more likely to occur in vaccinated chickens than in non-vaccinated chickens. There have been earlier reports of field isolates having sequences similar to IBDV vaccine strains (Ignjatovic & Sapats, 2002;Dolz et al, 2005;Jackwood et al, 2008;Hon et al, 2008). In the present study, the segment A region of the Georgia vaccine and other virulent classical IBDV strains isolated from the field and attenuated showed identical origin with classical IBDV strain D78, suggesting that the virulent field strains could be escaped mutants of vaccine strains.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, Tong et al (1993) showed that IBD was more likely to occur in vaccinated chickens than in non-vaccinated chickens. There have been earlier reports of field isolates having sequences similar to IBDV vaccine strains (Ignjatovic & Sapats, 2002;Dolz et al, 2005;Jackwood et al, 2008;Hon et al, 2008). In the present study, the segment A region of the Georgia vaccine and other virulent classical IBDV strains isolated from the field and attenuated showed identical origin with classical IBDV strain D78, suggesting that the virulent field strains could be escaped mutants of vaccine strains.…”
Section: Discussionsupporting
confidence: 50%
“…However, it has also been suggested that the recombination between different NDV strains is a rare event (Afonso, 2008) and that apparent genetic recombination in NDV may be an artifact (artificial recombination) (Song et al, 2011). Nevertheless, evidence of recombination between wild type and vaccine strains of NDV is relatively under-reported compared to other RNA viruses including avian influenza viruses (Webster et al, 1974), infectious bursal disease virus (Hon et al, 2008) and infectious bronchitis virus (Cavanagh et al, 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Some researchers argue that recombinants only represent a minor portion of the PCR amplicon and the resulting sequence is a consensus sequence of the overall population of amplicons and thus exclude this possibility of recombination [17]. However, previous studies have indicated that, for example, ∼5% of the 16S sequences within curated collections are anomalous or suspect, with chimeras accounting for the majority of problematic sequences [18].…”
Section: False Positive Recombination Signalsmentioning
confidence: 99%